Psychotic : Understanding Madness - Crowcroft, Andrew; Geis, Richard E (Portland, Ore. : Richard E. Geis, 1953)
was nominated for the 1956 Best Fanzine Hugo award; continued under title "Science Fiction Review"
Title from cover
Editor: Richard E. Geis
Volume numbering dropped after first issue
No. 1 also has volume numbering, i.e. Vol. 1, no. 1
Keywords: Fan magazines; Science fiction -- Periodicals